Assessment of the in vitro antibacterial activity of honey on some common human pathogens - CU, Anyanwu (Journal of Research in Biology, 2011)
The aim of the present study was to assess the in vitro antibacterial activity of bee honey on certain potentially pathogenic bacterial isolates. Different concentrations (10.0, 20.0, 40.0, 60.0, 80.0 and 100.0%) of honey sample were checked for their antibacterial activities, using disc diffusion assay, on some medically important bacteria including Escherichia coli, Klebsiella sp., Salmonella sp., Pseudomonas aeruginosa, Enterobacter sp., Staphylococcus aureus, and Proteus sp. The minimum inhibitory concentrations (MIC) of the honey sample were determined on the selected bacteria using agar dilution technique. The sample of honey showed pronounced bacterial inhibitory effect in vitro at honey concentrations of 40% and above on the various tested bacteria. No growth inhibition effect was observed at 10% concentration of honey. The MIC for the tested bacteria ranged between 12.5 and 25.0%. The MIC for Klebsiella sp. and S. aureus was 12.5% while for Proteus sp., the MIC was 25.0%. All the other tested bacterial isolates showed MIC value of 15%. The study shows that honey, like antibiotics, has certain organisms sensitive to it, and provides alternative therapy against certain bacteria and is also shown to have antibacterial action against a broad spectrum of bacteria, both gram- positive and gram-negative bacteria